The Shadow of Creusa : Negotiating Fictionality in Late Antique Latin Literature. - Cullhed, Anders (Beiträge zur Altertumskunde., 2015)
Anders Cullhed's studyexplores the early Christian confrontation with pagan culture as a remote anticipation of many later clashes between religious orthodoxy and literary fictionality. After a careful survey of Saint Augustine's long drawn-out farewell to ancient myth and poetry, Cullhed examines other Late Antique dismissals as well as appropriations of the classical heritage. Thus, The Shadow of Creusa elucidates a cultural conflict which was to leave traces all through the Middle Ages and beyond.